Repeated-batch lactic acid fermentation using a novel bacterial immobilization technique based on a microtube array membrane. (December 2019) - Chen, Chien-Chung; Lan, Chuan-Chi; Pan, Chorng-Liang; Huang, Mei-Ying; Chew, Chee-Ho; Hung, Chin-Chieh; Chen, Po-Hsuan; Lin, Hong-Ting Victor
Graphical abstract: Highlights: A novel cell immobilization technique for lactic acid production was introduced. Microtube array membrane was stable in lactic acid fermentation. MTAM-encapsulated lactic acid bacteria showed better lactic acid productivity. Abstract: Lactic acid has received considerable attention for its various applications. Although lactic acid is usually produced by batch fermentation using free microbes, repeated-batch fermentation using immobilized cells could offer several advantages over this method. In the present study, a novel bacteria immobilization technique using a renewable poly-L-lactic acid (PLLA) microtube array membrane (MTAM) was thoroughly evaluated in terms of its suitability for lactic acid fermentation. A bacteria encapsulation efficiency of 85–90% was obtained using a siphon approach, and bacteria in MTAMs with greater porosity showed greater lactic acid productivity. MTAM-immobilized Lactobacillus acidophilus were evaluated in eight cycles of repeated-batch lactic acid fermentation of commercial medium MRS (4% glucose) and red seaweed Gracilaria hydrolysate. The MTAM exhibited physical stability during lactic acid fermentation and improved glucose consumption and lactic acid production were achieved by immobilized cells. The immobilized bacteria showed a maximum C LA of 37.39 g/L, r P LA of 0.79 g/L·h, and Y L/S of 0.94 g/g in MRS fermentation, and a maximum C LA of 27.76 g/L, r P LA of 0.58 g/L·h, and Y L/S of 0.92 g/g in seaweed hydrolysate fermentation. Our data indicate that PLLA-MTAM is a novel, promising immobilization technology for lactic acid fermentation.